Weaning calves early - McKee, M.; Bolsen, K.K.; Schalles, R.R.; Conway, K.L.; Fink, G.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
Growth rate of 38 calves after being weaned at an average of 91.6 days was compared with growing rate of 37 calves averaging 91.2 days of age and continuing to nurse their mothers the same period. Average daily gains (lbs.) were 3.09 for the early weaned calves and 3.23 for those nursing their mothers the same 128 days. TDN consumption (lbs.) for each early-weaned calf and its mother for the 128-days from May 22 to September 27 was 2,714.8, and 3,215.2 for nursing calves and their mothers.
Keywords: Beef; Weaning; Average daily gains; Growth rate